Pengaruh Pengetahuan Dan Pengalaman Karyawan Terhadap Kualitas Produksi Ternak: Studi Di PT. Pelita Mulia Bersinar (International Forum of Researchers and Lecturers, 2025)
This study was conducted because the author saw the facts at PT Pelita Mulia Bersinar Each employee has different knowledge that is adjusted to their level of education, this is a determinant for the placement and success of the goals of the targets to be achieved by the company; The experience of employees certainly varies according to how long they have worked in the field which will indirectly form different thought patterns. In addition, it will also affect decision making to achieve the best quality of livestock production; The variety of employee socialization styles with partner farmers who have their own characteristics and different socialization models; and The achievement of livestock production quality in a company is fluctuating which is influenced by different employee competencies, in this case, influenced by different levels of employee knowledge and experience. The purpose of this study is to study, find out, and analyze the influence of employee knowledge on the quality of livestock production; the influence of experience on the quality of livestock production; and the influence of employee knowledge and experience on the quality of livestock production. While the method used in this study is an explanatory survey with a quantitative approach, while the technical data analysis, namely descriptive statistics Analysis and Inductive Statistics (Inferential) with correlation and multiple regression analysis tools. The results of the study and discussion show that employee knowledge has a positive effect on the quality of livestock production; experience has a positive effect on the quality of livestock production; and employee knowledge and experience have a positive effect on the quality of livestock production.